Optimization design of the hydro-pneumatic suspension system for highclearance self-propelled sprayer using improved MOPSO algorithm - Yang, Fan; Du, Yuefeng; Wen, Changkai; Li, Zhen; Mao, Enrong; Zhu, Zhongxiang (International Journal of Agricultural and Biological Engineering, 2024)
Large high clearance self-propelled sprayers were widely used in field plant protection due to their high-efficiencyoperation capabilities. Influenced by the characteristics of field operations such as high power, heavy weight, high groundclearance, and fast operation speed, the comprehensive requirements for the ride comfort, handling stability and roadfriendliness of the sprayer were increasingly strong. At the present stage, the chassis structure of the high clearance self-propelled sprayer that attaches great importance to the improvement of comprehensive performance still has the problems ofsevere bumps, weak handling performance and serious road damage in complex field environments. Therefore, this paperproposes an optimization design method for hydro-pneumatic suspension system of a high clearance self-propelled sprayerbased on the improved MOPSO (Multi-Objective Particle Swarm Optimization) algorithm, covering the entire process ofconfiguration design, parameter intelligent optimization, and system verification of the high clearance self-propelled sprayerchassis. Specifically, chassis structure of the hydro-pneumatic suspension suitable for the high clearance self-propelled sprayerwas designed, and a design method combining the improved MOPSO algorithm based on time-varying fusion strategy andadaptive update with the parameter optimization of hydro-pneumatic suspension based on this algorithm was proposed, andfinally the software simulation and bench performance verification were carried out. The results show that the optimized hydro-pneumatic suspension has excellent vibration reduction effect, and the body acceleration, suspension dynamic deflection andtire deflection were increased by 16.5%, 9.9% and 0.9% respectively, compared with those before optimization. Thecomprehensive performance of the hydro-pneumatic suspension designed in this study is better than that of the traditionalsuspension.Keywords: high clearance self-propelled sprayer, vibration reduction, hydro-pneumatic suspension, MOPSO, multi-objectiveoptimizationDOI: 10.25165/j.ijabe.20241702.7813Citation: Yang F, Du Y F, Wen C K, Li Z, Mao E R, Zhu Z X. Optimization design of the hydro-pneumatic suspension system for high clearance self-propelled sprayer using improved MOPSO algorithm. Int J Agric & Biol Eng, 2024; 17(2): 109–122